Application of rapid test kits for the determination of Amnesic Shellfish Poisoning in bivalve molluscs from Great Britain. (July 2016) - Johnson, Sarah; Harrison, Keith; Turner, Andrew D.
Abstract: Five commercial rapid screening methods for Amnesic Shellfish Poisoning were assessed for the analysis of naturally contaminated bivalve mollusc samples from GB. A range of shellfish species including mussels, scallops, clams, oysters and cockles, both positive and negative for domoic acid were assessed, with kit performance measured through comparison with the reference HPLC-UV method. Two lateral flow immunoassays manufactured by Neogen and Scotia Rapid Testing Ltd, were both found to provide a simple and accurate qualitative detection of ASP in shellfish. No false negative or false positive results were returned by either assay. The Scotia method showed the additional advantage of providing a numerical result which was found to correlate well with domoic acid concentration, thus providing a useful additional semi-quantitative aspect to the testing. Three ELISA kits, supplied by Beacon, Biosense and Bioo Scientific were all found to provide a good qualitative indication for the presence of domoic acid. Quantitative results varied between the three assays. The Beacon assay was the only kit to return no false negative results for samples containing domoic acid at concentrations above the maximum permitted regulatory limit of 20 mg/kg, but with, on average, a slight over-estimation of toxin concentrations. Both the Biosense and, more notably, the Bioo Scientific kits tended to under-estimate toxin levels, with both assays also returning false negative results. All methods were relatively straightforward to use, with the lateral flow assays in particular providing a simple and rapid methodology suited to those with no access to laboratory equipment. Whilst the data has provided some evidence for suitability for indicative testing for some species of bivalve shellfish from GB, further work would ideally be required using a larger number of test kit batches on a greater number of samples for any method being utilised safely for routine testing. Highlights: Domoic acid in Great Britain. Application of immunochromatography. ELISA test kits. Comparison of rapid methods.